Management of Alternaria leaf blight (Alternaria polianthi) of tuberose (Agave amica) - Sonavane, Priti; T, Usha Bharathi (Journal of Horticultural Sciences, 2024)
Tuberose (Agave amica) is a perennial bulbous crop widely cultivated across the globe for its attractive and sweetly scented flowers used for loose flower, cut flower, perfume manufacture, essential oil production, and decoration. Alternaria leaf blight disease caused by Alternaria polianthi is a major limitation in tuberose cultivation. A field experiment was formulated to evaluate six fungicides against Alternaria polianthi causing leaf blight in tuberose. Results indicated that Difenconazole 25EC was the most effective with disease severity (11.13) compared to other treatments, followed by Tebuconazole 2DS. Tebuconazole 2DS and Azoxystrobin 23SC were the most effective in increasing the number of flowers per spike and spike length. Difenconazole 25EC also showed high effectiveness, particularly in spike length.